Integrating social equity in sustainable development practice: Institutional commitments and patient capital. (August 2018) - Trudeau, Dan
Highlights: Qualitative research on the inclusion of affordable housing in development projects. Focus on how social equity operates in tension with concerns of livability. Promoting social equity requires government institutions plan for it from the start. Success depends on patient capital and interest in nonmaterial returns on investment. Promoting equity hinges on its perception as contributing to livability. Abstract: Sustainable urban development is widely conceptualized as resulting from a balance of economic, environmental, and social equity concerns. Yet, critics argue that social equity is routinely left out in development practice. Aiming to help identify solutions that can address this problem, this paper examines sustainable development projects that have managed to incorporate social equity in substantive ways into development practice. Drawing on case study research of nine neighborhood-scale development projects distributed across three metropolitan areas in the United States – Austin, Denver, and Minneapolis-St. Paul – this article examines the contexts and processes that enable the incorporation of social equity into sustainable development practice. Using data from intensive interviews with actors that shaped the development of mixed-use and transit-oriented neighborhoods designed according to the New Urbanism planning movement, the article investigates three storylines that illustrate different ways that social equity concerns are left out, marginalized, or integrated into development practice. Comparison of the processes driving each storyline shows that integrating social equity in sustainable development can succeed when there is an institutional effort to champion social equity and where that effort brings patient capital and provides conceptual resources that help link social equity to concerns of livability.